TO THE ISSUE OF THE “VALIDITY” OF THE MARXIST LABOR VALUE THEORY - Yu. A. Kropin (Финансы: теория и практика, 2017)
The paradox of the current state of the economic education is that many theoretical provisions taught at universities are based on a theory the use of which in the recent historical past led to a systemic crisis in the development of the country. The issue in question is the Marxist theory of the labor value that regards money as a “universal equivalent”. The lack of critical re-evaluation of this theory under modern conditions is not just to the detriment of the development of the country’s monetary and banking system, in fact it already has negative consequences. Hence the actual task is to show the “validity”, or rather, the failure of this theory not only for the current stage of market development but going back to its roots. This is the purpose of the paper. Methodology. This study is not a hasty impromptu but the result of many years of reflection on various aspects of the Marxist theory which in its final form was set forth by K. Marx in the first volume of Capital. Therefore, this source was the main object of research and, accordingly, citation in the paper. The basic research methods included the dialectical method, the method of organic sequences and a number of other general and special scientific methods. Results. The most important result of the paper is the critical re-evaluation of the Marxist theory of the labor value and the positioning of money as a “universal equivalent”. Conclusions. The Marxist understanding of a commodity as a unity of the use value and the exchange value is far-fetched. Commodities and money have nothing in common that would allow drawing parallels between them and carrying out market transactions on sort of an equivalent basis. Accordingly, money cannot be positioned as a “universal equivalent”. The Marxist understanding of the essence of money outlined in many student courses of today must be overcome. However, such overcoming should take place not through a ban or by simply ignoring the Marxist theory, which due to its specifics still has an almost hypnotic effect on the minds of many economists, but through a scientific analysis of its nature.